Role of Novel Drug Delivery Vehicles in Nanobiomedicine 2020
DOI: 10.5772/intechopen.88268
|View full text |Cite
|
Sign up to set email alerts
|

Solid Lipid Based Nano-particulate Formulations in Drug Targeting

Abstract: Recently, targeted drug delivery systems have gained much more interest for delivering varieties of drugs as well as imaging agents specifically to the targeted disease cells or tissues. These are well known for their increased precision and accuracy in mode of drug delivery along with reduced side effects. Though numerous carriers are being employed for drug targeting, the solid lipid based nanoparticles (SLNs) are preferred over them owing to their ability to encapsulate wide varieties of drugs, biocompatibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…It was reported that lung targeting in speci c "the deep lung" confronts a crucial challenge, namely the premature mucocilliary clearance. Ligand-anchored drug delivery system aim at achieving enhanced sitespeci c drug delivery as well as reduced reticular endothelial system (RES) uptake [6,7] . However, the clinical success of such an approach depends on the selection of appropriate ligands lacking immunogenic potential with the ability to mediate cargo internalization by the target cell [8] .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that lung targeting in speci c "the deep lung" confronts a crucial challenge, namely the premature mucocilliary clearance. Ligand-anchored drug delivery system aim at achieving enhanced sitespeci c drug delivery as well as reduced reticular endothelial system (RES) uptake [6,7] . However, the clinical success of such an approach depends on the selection of appropriate ligands lacking immunogenic potential with the ability to mediate cargo internalization by the target cell [8] .…”
Section: Introductionmentioning
confidence: 99%